ANALYSIS OF RAIL TRANSPORT ACCIDENTS USING ONE-WAY ANALYSIS OF VARIANCE - Motyková, Jana; Švadlenka, Libor (My University, 2016)
The article deals with the analysis of rail transport accidents in the period of 2008 – 2015 and with the comparison of their causes. The existence of a relationship between causes of accidents and calendar months when the accidents have occurred was determined by using one-way analysis of variance.
Analýza mimořádných událostí v železniční dopravě pomocí jednofaktorové analýzy rozptylu
Keywords: rail transport; accidents; one-way analysis of variance; železniční doprava; mimořádné události; jednofaktorová analýza rozptylu